MENGUKUR DAMPAK RETURN ON ASSET DAN PERPUTARAN PERSEDIAAN TERHADAP HARGA SAHAM INDEKS LQ45 DI BEI - Furniawan (The Asia Pacific Journal Of Management Studies, 2024)
This study aims to analyze the impact of Return on Assets (ROA) and Inventory Turnover on stock prices of companies listed in the LQ45 index on the Indonesia Stock Exchange. The analytical method used in this research is multiple linear regression analysis to examine the partial and simultaneous effects between the independent variables (ROA and Inventory Turnover) and the dependent variable (stock prices). The results of the study show that, partially, Return on Assets (ROA) has a significant impact on stock prices. This indicates that an increase in financial performance, as measured by ROA, tends to raise the company's stock prices. Conversely, Inventory Turnover does not have a significant impact on stock prices, suggesting that the efficiency of inventory management does not directly influence market valuation of the company’s stock price. However, simultaneously, ROA and Inventory Turnover have a significant impact on stock prices. These findings underline the importance of considering both factors together in assessing company performance and their effect on stock prices in the capital market. This research provides valuable insights for investors and company management in understanding the financial factors that influence stock prices, and it can be used as a reference in making investment decisions and business strategies.